SIKAP NEGARA-NEGARA ANGGOTA UNI EROPA DALAM MENANGANI KRISIS YUNANI (Studi Kasus : Sikap Jerman, Perancis dan Inggris) - Triesanto Romulo Simanjuntak; Dafri Agussalim (Cakrawala Jurnal Penelitian Sosial, 2014)
European economic integration and unity of this currency leaves form a very significant ketegantungan among its members, so that a crisis was enough to shake the stability between the countries members of the other. Basically the single currency system seems to be double-edged blade for the European Union. On the one hand so profitable and increase the bargaining positions of European countries, but on the other hand is potentially detrimental. One reason is because of the level of adaptation of a State. Not all countries have a great economy to enter the euro zone. The existence of this single currency system to make the countries in the European Union will become vulnerable to a crisis. This is what led to the crisis that occurred since 2008 is so easily spread to countries in Europe.This research focuses on the policy decision taken by the third country in the European Union, namely Germany, France and the United Kingdom. Domestic political factors of history, and also the economic power of these countries also affect how the policy making process to rescue Greece from the crisis that is increasingly spreading to other European countries. The main purpose of the discussion of this paper is to provide new information concerning the handling of crisis from a process whereby policies domestic factors also gives countries a great influence, it also gives a view that Constructivist Theory is able to provide a view of the case.Keywords: EU, Euro, Greece, Germany, France, United Kingdom, crisis, policy.